2011
DOI: 10.1253/circj.cj-10-0719
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Magnetic Resonance Imaging-Based Finite Element Analysis for the Biomechanical Stress Analysis of Hemorrhagic and Non-Hemorrhagic Carotid Plaques

Abstract: Background: Biomechanical stress analysis has been used for plaque vulnerability assessment. The presence of plaque hemorrhage (PH) is a feature of plaque vulnerability and is associated with thromboembolic ischemic events. The purpose of the present study was to use finite element analysis (FEA) to compare the stress profiles of hemorrhagic and non-hemorrhagic profiles. Methods and Results:Forty-five consecutive patients who had suffered a cerebrovascular ischemic event with an underlying carotid artery disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In a MRI-based study involving 45 symptomatic patients, the stress level over FC in 28 individuals with PH was significantly higher than those of asymptomatic patients (315 kPa [247–434] vs. 200 kPa [171–282]; p =0.003; median [inter quartile range]) (Sadat et al, 2011b). Similarly, Huang et al (2010) performed 3D FSI on 5 patients showing that stress over FC near PH was higher than those locations without PH (75.6 kPa vs. 68.1 kPa; p =0.0003).…”
Section: Local Biomechanical Stresses and Carotid Plaque Hemorrhagementioning
confidence: 99%
“…In a MRI-based study involving 45 symptomatic patients, the stress level over FC in 28 individuals with PH was significantly higher than those of asymptomatic patients (315 kPa [247–434] vs. 200 kPa [171–282]; p =0.003; median [inter quartile range]) (Sadat et al, 2011b). Similarly, Huang et al (2010) performed 3D FSI on 5 patients showing that stress over FC near PH was higher than those locations without PH (75.6 kPa vs. 68.1 kPa; p =0.0003).…”
Section: Local Biomechanical Stresses and Carotid Plaque Hemorrhagementioning
confidence: 99%
“…There are several studies that provide evidence for the existence of intraplaque hemorrhage or lipid necrotic cores within carotid plaques. These are based on histology, 10,11,[16][17][18] ultrasound, 14,19 and magnetic resonance imaging 5,20,21 of the plaques. Large pressure drops across a stenosis can act directly, 22 or can apply shear stress to the plaque manifesting as tensile stress at the proximal edge or shear stress within the plaque, [23][24][25] to cause plaque disruption; while Bernoulli pressure depression due to high velocities within a stenosis may promote intraplaque hemorrhage.…”
mentioning
confidence: 99%
“…The biomechanical propriety of IPH might play a role in the vulnerability of plaque surface 18 ) . It has been shown that IPH had a close connection with enhanced stress over fibrous cap 19 , 20 ) . According to previous investigators, because of the different ingredients appearing during aging of IPH, the mechanical impact of IPH on fibrous cap will change dynamically.…”
Section: Discussionmentioning
confidence: 97%